Pengaruh Literasi Keuangan, Motivasi Investasi Dan Kemampuan Finansial Terhadap Minat Investasi (Studi Kasus Pada Anggota Muslimat Nahdlatul Ulama Kota Malang Yang Mengikuti Kegiatan Literasi Keuangan & Inklusi Pasar Modal Bagi 1500 Muslimat NU Se-Kota Malang) - Rodhifan, Muhammad Bagus; Basalamah, Muhammad Ridwan; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to analyze and assess the effect of financial literacy (X1), investment motivation (X2), and financial capability (X3) on investment interest, both partially and simultaneously. The research method used is a quantitative approach. The sample of this study were 94 members of Muslimat Nahdlatul Ulama Malang City who had participated in Financial Literacy & Capital Market Inclusion activities from a population of 1500 people. The questionnaire was used as a data collection instrument, Validity Test and Reliability Test were used to measure the performance of the instrument. Not only that, this study also uses Normality Test, Multicollinearity Test, Heteroscedasticity Test, Multiple Linear Regression Analysis, F Test, R2 Test, and t Test. The results of this study indicate that financial literacy, investment motivation, and financial capability simultaneously have a positive and significant effect on investment interest. Partially, financial literacy and investment motivation have a positive and significant effect on investment interest, while financial capability partially has no positive and no significant effect on investment interest. Keywords: Financial Literacy, Investment Motivation, Financial Capability, Investment Interest.